The impact of the board of directors as a governance mechanism on the financial Distress of companies -Empirical Evidence from Algerian companies (2017-2021)- - hassnaoui, rabia; boudjettou, hakim (Journal of Research in Finance and Accounting, 2025)
The present study aims to examine corporate governance's impact on the likelihood of financial distress for a sample of 150 observations of 30 non-financial companies in Algeria over the period 2017-2021. To assess the Impact of corporate governance, the current study constructs three Board characteristics as independent variables, such as CEO duality, board ownership, and board size and two characteristics of companies (financial leverage, company size) as control variables. The Altman Z-score is used to measure financial distress. The panel Logistic Regression technique is used to conduit the relationship between corporate governance and financial distress of companies. Result reveals that CEO duality show significant positive impact on financial distress, while board ownership shows significant negative impact; however, it shows that the size of the board of directors has no significant effect on financial distress. The study also provided evidence that some characteristics of the company, such as the size of its assets and the rate of financial leverage, can be useful in determining the possibility of exposure to financial distress.